2020
DOI: 10.3390/molecules25112652
|View full text |Cite
|
Sign up to set email alerts
|

Mentha piperita L. Micropropagation and the Potential Influence of Plant Growth Regulators on Volatile Organic Compound Composition

Abstract: Due to the industrial use of Mentha piperita L. (peppermint), it is important to develop an optimal method to obtain standardized plant material with specific quality parameters. In vitro cultures may allow the production of desirable odor-active compounds (OACs) and improve their share in the plant aroma profile. There are two types of explants that are commonly used, apical meristems and nodal segments. In this study, the best overall effects were shown to be produced by the combination of MS medium with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Tissue culture also provides various avenues wherein the plant's metabolic pathways can be manipulated, resulting in in vitro plants with increased secondary metabolic content. Previous studies have shown similar results in Mentha, which when grown in MS media, supplemented with indole-butyric acid (Lyczko et al 2020) showed higher accumulation of odor active and volatile compounds.…”
Section: Introductionsupporting
confidence: 72%
“…Tissue culture also provides various avenues wherein the plant's metabolic pathways can be manipulated, resulting in in vitro plants with increased secondary metabolic content. Previous studies have shown similar results in Mentha, which when grown in MS media, supplemented with indole-butyric acid (Lyczko et al 2020) showed higher accumulation of odor active and volatile compounds.…”
Section: Introductionsupporting
confidence: 72%
“…The major representatives (more than 4.00%) were pyridine (3.10% ± 0.07), ( Z )-3-hexen-1-ol (16.48% ± 0.31), ( E )-3-hexen-1-ol acetate (19.99% ± 0.01), p -cymene (4.96% ± 0.02), ( E )-α-bergamotene (4.15% ± 0.19), β-caryophyllene (11.30% ± 0.27) and labda-8(20),13(16),14-triene (4.89% ± 0.09)., which may be found in other, various species like Lavandula angustifolia Mill. [ 24 ], Coriandrum sativum L. [ 25 ], Mentha piperita L. [ 26 ], Cannabis sativa L. [ 27 ] and Boletus edulis [ 28 ]. Especially interesting was high content of ( E )-α-bergamotene, which is characteristic for Citrus bergamia Risso fruit [ 29 ] and pyridine, which was reported in similar amounts in Cicer arietinum L. [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[16,[20][21][22][23][24]. The use of growth regulators increases the production of EOs by peppermint plants and affects the chemical composition of EOs [18,22,[25][26][27]. The amount of the individual components contained in the EOs changes and undesirable substances are not synthesized, which was confirmed by the experiment of Bertoli et al [20].…”
Section: Introductionmentioning
confidence: 90%
“…The cv Tik-Tak had the maximum multiplication factor and cv Serebristaya had the minimum. Full MS medium supplemented with 1.0 mg•L -1 IBA is optimal for in vitro root induction in mint [17,22,40]. A number of studies have found that mint shoots can form roots spontaneously [41,42].…”
Section: In Vitro Culturesmentioning
confidence: 99%
See 1 more Smart Citation